Interobserver variability in the histopathological classification and grading of dysplasia in elevated colon lesions in the city of Lima - Gallegos Serruto, Guido (2024)
Colonic polyp refers to lesions that exhibit a protrusion of the mucosa, regardless of histology. The most recent WHO classification is based on a better understanding of these lesions; however, its application in daily practice could be subject to interobserver variability biases that could have clinical implications. Objectives: To determine the interobserver variability in the histopathological reporting and grading of dysplasia of samples obtained from elevated colon lesions in a private laboratory in the city of Lima. Materials and methods: Observational, descriptive, and prospective study: Case series type. All biopsies of elevated colon lesions received over a period of 3 months were evaluated by two observers without clinical information of the cases, to diagnose the lesions according to the WHO classification. In cases of diagnostic differences, the cases were evaluated together to reach a consensus. Results: A Kappa coefficient value of 0.458 was obtained in the diagnostic classification of elevated colon lesions, while a Kappa value of 0.416 in the evaluation of dysplasia; indicating moderate agreement. Conclusions: Despite achieving moderate agreement between evaluators, this work demonstrates the importance of not only relying on morphological criteria for diagnostic classification, but also including criteria of location and size of these lesions to increase diagnostic accuracy.